Investors' valuation of global product design and development - Ojah, K; Monplaisir, L (Journal of International Business Studies, 2003)
Stock price responses to 170 announcements about global product design and development (GPDD) by NYSE, AMEX, and Nasdaq firms are significantly positive. This indicates that GPDD, which is fast becoming a strategic initiative of choice for multinational firms in the face of globalization and short time-to-market, is value-enhancing. The value enhancement is strong when announcing firms have a high level of information technology/systems infrastructure and a wide geographical spread of operation, and respond aggressively to their peers' strategic initiatives. Further, cross-sectional analyses show that firms' product market structure, their peers' competitive strategy posture, and whether they produce a good or a service, jointly determine the variation of excess returns attributable to global product development.